Christ circumcised : a study in early Christian history and difference - Jacobs, Andrew S., 1973- (Divinations., 2012)
This first full-length study of Jesus' circumcision reimagines the language of difference and identity in early Christianity. From his earliest appearance in the Gospel of Luke to the medieval Feast of the Circumcision, Christ circumcised embodies a new way of imagining Christians and their creation of a new religious culture.